Direct synthesis of dimethyl carbonate from CO2 and methanol over trifluoroacetic acid modulated UiO-66. (October 2018) - Xuan, Keng; Pu, Yanfeng; Li, Feng; Li, Aixue; Luo, Jing; Li, Lei; Wang, Feng; Zhao, Ning; Xiao, Fukui
Graphical abstract: Highlights: UiO-66-X for the direct synthesis of DMC from CO2 and methanol. TFA modulation increased the amount of active sites in UiO-66-X. TFA modulation improved the catalytic activity of UiO-66-X. The reaction mechanism for DMC synthesis over UiO-66-X was proposed. Abstract: A series of trifluoroacetic acid (TFA) modulated metal-organic frameworks UiO-66 catalysts were synthesized for the direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol in this work. Characterization results show that the surface area, pore size, pore volume as well as the amount of missing-linker defects, Lewis acid site, Lewis basic site and hydroxyl of UiO-66-X can be tuned by regulating the amount of TFA modulator. Catalytic activity assessments reveal that TFA modulation enhanced the activity of UiO-66-X. The catalytic activity improvement of the UiO-66-X could be attributed to the increased amount of active sites and the enlargement of porosity originated from TFA modulation. Moreover, a possible reaction mechanism for DMC synthesis from CO2 and methanol over UiO-66-X was proposed based on the in situ FT-IR results.